Differentiation Treatment Of KBIHU According To The Law On Hajj And Umrah Management - Agil Syarifatul Mashohih; Abdul Rozaq (Fakultas Syariah INSURI Ponorogo, 2026)
The regulatory transformation of Hajj management in Indonesia through the enactment of Law Number 14 of 2025, amending Law Number 8 of 2019, has significantly impacted (KBIHU)as a strategic partners of the government. This study aims to analyze the differentiation of regulatory treatment for the word KBIHU under both legal regimes and to examine its managerial implications for institutional accountability and professionalism. Employing a qualitative comparative document analysis, this research focuses on Articles 52-56 of both laws to identify shifts in legal norms. The findings reveal a governance paradigm shift from a socio-religious partnership model to a more standardized, bureaucratic oversight system. Key changes include stricter accreditation requirements, digital supervision through the SERAMBI platform, an increase in the pilgrim-to-guide ratio from 1:135 to 1:151, and a shift in guide quota allocation from an automatic entitlement to a proposal-based mechanism dependent on competency selection. While the new regulation promotes transparency and professional standards, the increased workload per guide potentially risks reducing the quality of personalized guidance. Consequently, KBIHU is required to reposition its service strategies to remain adaptive within an increasingly regulated and modernized Hajj and Umrah management ecosystem.